Teknologi Aplikasi Nurse Call berbasis Client Server Pada Rumah Sakit - Cahya Vikasari; Purwiyanto Purwiyanto; Galih Mustiko Aji (Politeknik Negeri Batam, 2018)
The credibility of a hospital has the effect of the services provided by the hospital. One of the services in the hospital is inpatient services and the role of nurses who have an important role in serving patients. Some problems in hospitalization services that occur such as manual nurse calls are done by visiting the treatment room and proposing the desired service. This method is less effective because it will require a long process in service. The application of nurse calls is done to improve services so that nurses can provide the best service and patient health can be monitored properly. The calling system for nurses is based on client-server and additional features such as heart detection, temperature detection, and emergency buttons that have the role to call nurses. The advantage of the nurse call application is that it can monitor patient health from several detection devices that will automatically call through the application. In addition to handling patients will be monitored by the hospital, the nurse's performance will also be detected. The results of this study are that the nurse call process will be automatically carried out by a detection device so that the nurse will detect the patient's condition quickly, the patient handling data will be stored on the server, therefore the history of heart rate and temperature records is more complete and can be used for doctors to handle patients.